Trends in Nutrition Outcomes, Determinants, and Interventions in India (2006–2016) - Menon, Purnima; Nguyen, Phuong Hong; Mani, Sneha; Kohli, Neha; Avula, Rasmi; Tran, Lan Mai (International Food Policy Research Institute, 2017)
This report aims to provide a general overview of national trends and of state-level variability in nutrition outcomes, determinants, and intervention coverage, thus helping to identify areas of progress and areas where more investment is critical to accelerate progress. Using data available at the time of analysis and writing, the goal of this report is to bring together data to support policy decisions for nutrition at the national level and across multiple states.